2008
DOI: 10.1364/oe.16.016854
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid fiber gratings coated with a catalytic sensitive layer for hydrogen sensing in air

Abstract: Using hydrogen as fuel presents a potential risk of explosion and requires low cost and efficient leak sensors. We present here a hybrid sensor configuration consisting of a long period fiber grating (LPFG) and a superimposed uniform fiber Bragg grating (FBG). Both gratings are covered with a sensitive layer made of WO(3) doped with Pt on which H(2) undergoes an exothermic reaction. The released heat increases the temperature around the gratings. In this configuration, the LPFG favors the exothermic reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…Among others, gas sensing (Buric et al, 2007;Caucheteur et al, 2008), humidity sensing (Kronenberg et al, 2002;Yeo et al, 2005), salinity Men et al, 2008), magnetic field (Davino et al, 2008;Yang et al, 2009) and pH monitoring (Corres et al, 2007) have been recently reported. Based on a similar principle, the association of an absorbing layer to a FBG can be realized for infrared (IR) radiation detection purposes as it has been demonstrated in (Caucheteur, 2010;Renoirt, 2010;Yüksel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, gas sensing (Buric et al, 2007;Caucheteur et al, 2008), humidity sensing (Kronenberg et al, 2002;Yeo et al, 2005), salinity Men et al, 2008), magnetic field (Davino et al, 2008;Yang et al, 2009) and pH monitoring (Corres et al, 2007) have been recently reported. Based on a similar principle, the association of an absorbing layer to a FBG can be realized for infrared (IR) radiation detection purposes as it has been demonstrated in (Caucheteur, 2010;Renoirt, 2010;Yüksel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At present there are several kinds of optical fiber hydrogen sensors, such as evanescent sensor [1][2][3][4][5][6], micro-mirror sensor [7][8], surface plasmon resonance (SPR) sensor [9], acoustic resonator sensor [10], and fiber Bragg grating (FBG) sensor [11][12][13][14]. Although the evanescent and micro-mirror sensors are simple and inexpensive, their multiplexing capability is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…At present the most sensitive FBG hydrogen sensor is based on WO 3 doped with Pt undergoing an exothermic reaction in hydrogen atmosphere [13]. The sensor features fast response and high sensitivity, but it still has the potential to explode in high concentrations of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the explosion-proof nature of optical fiber, many Pdcoated optical fiber sensors have been demonstrated for single-point hydrogen sensing, including Pd-coated mirror, 1 side-polished and tapered fiber sensor, 2,3 Fabry-Perot interferometer (FPI), 4 and fiber Bragg gratings (FBGs). [5][6][7][8] To enhance the hydrogen absorption rate of Pd in low temperature, different in-fiber heating techniques have been developed using long period grating (LPG), 5 double-clad fiber (DCF), 6 and high attenuation fiber (HAF). 7,8 A more challenging issue is to develop distributed sensing technology, so sophisticated hydrogen system can be completely monitored using a single interrogation unit.…”
mentioning
confidence: 99%
“…Temperature crosssensitivites can be discriminated from the hydrogen strain responses by employing polarization maintained fiber as FUT. 14 Furthermore, using multimode fibers and high attenuation fibers, optical on-fiber heating [5][6][7][8] can be employed instead of electrical heating to completely eliminate the spark hazard, but the sensing length is limited to 100-200 mm long and uniform heating profile cannot be guaranteed. In our opinion, this paper demonstrates a fully distributed all-fiber hydrogen sensing solution with good prospects for practical applications.…”
mentioning
confidence: 99%